Salivary glutathione in bipolar disorder: A pilot study - Ngamchuea, K; Batchelor-McAuley, C; Williams, C; Godlewska, BR; Sharpley, AL; Cowen, PJ; Compton, RG (Elsevier, 2018)
Background Glutathione (GSH) is an important cellular antioxidant and its levels are decreased in some studies of bipolar patients. Saliva provides a simple and feasible means of measuring GSH but has not yet been applied to the study of bipolar disorder. The purpose of the study was to compare salivary levels of GSH and oxidized glutathione (GSSG) in bipolar patients and healthy controls. Methods Saliva was sampled from 22 medicated, euthymic patients with bipolar disorder and 20 healthy controls. GSH and GSSG were measured using an enzyme kinetic essay. Results GSH and GSSG were significantly higher in saliva from bipolar patients relative to controls. The ratio of GSH:GSSG was unchanged. There was no correlation between the measured clinical characteristics of the patients and GSH levels. Limitations The main limitation of the study was the small sample size. Patients were medicated which may have influenced saliva production and hence GSH levels. In addition, salivary GSH may not reflect GSH status in tissues more directly involved in the pathophysiology of bipolar disorder. Conclusion Salivary GSH can be readily measured in bipolar patients. Relative to controls, salivary levels of GSH and GSSG were increased in bipolar patients but their ratio was unchanged. The origin and significance of these change requires further study.